Electrospinning Nanotechnology-A Robust Method for Preparation of Nanofibers for Medicinal and Pharmaceutical Application. - Meghana, Bhadarge; Umesh, Dhas; Abhay, Shirode; Vilasrao, Kadam (Asian Journal of Pharmaceutical Research and Development, 2020)
Nanotechnology has evolved as a preferred choice in current research arena due to the advantages offered by it. The current research in pharmaceutical development is all about exploring and/or adopting different approaches for preparation of nanostructured drug delivery systems. Electrospinning nanotechnology has made its mark as a technology of choice for preparation of nanofibers for different applications. Electrospinning is a novel, robust and efficient fabrication process that is widely accepted and used to assemble nanofibers with distinct features such as length of several kilometers and diameter less than 300 nm. One of the most striking features of nanofibers is that they provide exceptionally high surface area-to-volume ratio and high porosity, making them a robust and attractive candidate for many advanced applications. Many researchers working on development of medicinal and pharmaceutical product design and development have reported their studies indicating successful implementation of electrospinning nanotechnology for preparation of nanofibers with distinct medicinal and pharmaceutical drug delivery applications. Authors of this article aims to provide a comprehensive review of electrospinning method for preparation of nanofibers with respect to theoretical principle, mechanics of electrospinning, critical process parameters, polymers and drug loaded nanofibers incorporated in different drug delivery systems for various pharmaceutical application.